Dinoflagellate cyst biostratigraphy of Miocene strata in the Adana Basin, Eastern Mediterranean, Turkey - Turkecan, Aksel Tugba; Munsterman, Dirk; Isik, Ugras; Altıner, Demir; Pinar, Mehtap; Cevik, Tugba; Alay, Zeynep (Palynology, 2018)
The Adana Basin is one of the major Neogene basins situated in SW Turkey with sedimentary successions providing good records of the paleoenvironmental changes that affected the Mediterranean area. Since a detailed biochronostratigraphic framework has not been properly established in the Adana Basin yet, this study will be the first multidisciplinary approach carried out in this region. In addition, a detailed biozonation based on marine palynomorphs was the first ever documented from the Kopekli Formation deposited during the Miocene (from late Burdigalian to Langhian) and the established biozones were correlated with those of planktonic foraminifera and calcareous nannofossils. According to the first occurrences (FOs) and the last occurrences (LOs) of selected taxa, five biozones (P-1, P-2, P-3, P-4 and P-5) based on dinoflagellate cysts; five biozones (M4a, M4b, M5a, M5b and M6) based on planktonic foraminifera; and two biozones (NN4 and NN5) based on calcareous nannofossils were established in the Miocene Kopekli Formation. In order to achieve a worldwide biostratigraphic perspective based on dinoflagellate cysts, the present biozones were compared with those described from NW Europe (Denmark, Germany, the Netherlands), the East Coast of the US and Egypt. After calibration to the established Turkish foraminifera and nannofossils standard, the palynological analysis shows that the recorded dinoflagellate cysts events (e.g. FO of Labyrinthodinium truncatum, Cerebrocysta poulsenii and Unipontidinium aquaeductus and LO of Palaeocystodinium ventricosum) occurred chronostratigraphically earlier in SE Turkey than in NW Europe and on the East Coast of the US.